Exploring the Relationship of Form and Hierarchy from the Perspective of Architectural Space and Components Taking the Mandarin’s House in Macau as an Example - Yile Chen; Junzhang Chen (PT FORMOSA CENDEKIA GLOBAL, 2022)
In Macau, China, there are still many traditional buildings built at the end of the 19th century. Among the traditional residential buildings with Lingnan style, the Mandarin’s House is the largest, covering an area of 4,000 square meters. It consists of a number of buildings of different styles and open spaces. There are more than 60 large and small rooms. It is a rare family-style building complex in Macau. The building has a depth of more than 120 meters along the direction of Rua da Barra. The gate building, the servant room building and the two juxtaposed courtyard buildings behind the main gate building are arranged in sequence. In the 1950s and 1960s, the descendants of the Zheng family lived in different places and developed independently. Many spaces in the Mandarin’s House were sub-leased, and at one time more than 300 people lived in it. The scene of